Infarction of the lingula following left upper lobe trisegmentectomy. (January 2016) - Brunswicker, Annemarie; Farid, Shakil; Van Tornout, Filip
Anatomical segmentectomy has emerged as the procedure of choice for early-stage non-small-cell lung cancer, especially in the presence of poor cardiopulmonary reserve. The most common postoperative complications are pneumonia, persistent air leak, and rarely, vascular compromise of the remaining lobe. We report the case of a 74-year-old woman who underwent thoracotomy and left upper lobe trisegmentectomy for T1bN0Mo squamous cell carcinoma and subsequently developed infarction and hepatization of the remaining lingula. A completion left upper lobectomy was performed and the patient made a full recovery.